Cost of Dual-Task Performance in Tactile Perception Is Greater for Competing Tasks of the Same Type. (May 2020) - Nguyen, Dacey; Brown, James; Alais, David
This study examines dual-task performance in the tactile modality and tests whether dual-task cost depends on task type. Experiment 1 involved competing tasks of the same type, using a primary localisation task on the left hand and a secondary localisation task on the right hand. In Experiment 2, the primary task on the left hand remained the same, while an intensity discrimination task was used as the secondary task on the right hand. Subjects in both experiments completed three conditions: the primary task alone, a dual-task condition, and the primary task with the secondary stimulus present but no response required. Across both experiments, performance on the primary task was best when it was presented alone, and there was a performance decrement when the secondary stimulus was present but not responded to. Performance on the primary task was further decreased when participants had to respond to the secondary stimulus, and the decrease was larger when the secondary task was localisation rather than discrimination. This result indicates that task type in the tactile modality may modulate the attentional cost of dual-task performance and implies partially shared resources underlie localisation and intensity discrimination.